Pengaruh Aplikasi Asam Humat dan Pupuk N, P, dan K Terhadap Pertumbuhan dan Produksi Jagung Manis (Zea mays L. saccharata) - Indiarto, Gunawan; Widjajanto, Didik Wisnu; Lukiwati, Dwi Retno (JURNAL AGROPLASMA, 2022)
This study was aimed to determine the effect of humic acid, N, P, and K fertilizer and the interaction of the two treatments on the growth and production of sweet corn. The field experiment was carried out on August 02 â€“ October 12, 2021 in Tembalang Sub-district, Semarang City and at the Ecology and Plant Production Laboratory, Faculty of Animal and Agricultural Sciences, Diponegoro University, Semarang (7o03â€™17â€ S dan 110o26â€™28â€ E). The factorial experiment with a 3 x 3 randomized block design with 3 replications was used in the study. The first factor was consisted of 20, 25, and 30 kg of humic acid/ha, respectively for M1, M2 and M3.The second factor was the dose of fertilizer N, P, and K which consisted of 100%, 75%; and 50% of the recommended dose, for P1, P2 and P3 respectively.The 100% of recommended dose was200 kg N/ha, 154 kg P2O5/ha, 125 kg K2O/ha. Parameters observed consisted of plant height, number of leaves, number of cobs, and weight of cobs. The data obtained were analyzed by using analysis of variance (ANOVA) and Duncan's test at 5% was used for further analysis. The results showed that the dose of humic acid had a significant effect on the parameters of plant height and number of leaves. Â Keywords: dose, humic acid, sweet corn